Gander, Hans-Helmuth. SelfUnderstanding and Lifeworld. Basic Traits of a Phenomenological Hermeneutics. Trans. Ryan Drake and Joshua Rayman. Bloomington: Indiana University Press, 2017. 415 pp. (2020)
COL0064191